Investment Valuation : Tools and Techniques for Determining the value of Any Asset : University Edition - Aswath Damodaran (John Wiley & Sons, 2012)
This book provides expert instruction on how to value virtually any type of asset-stocks, bonds, options, futures, real assets, and much more. This reliable resource uses real-world examples and the most current valuation tools to guide through the theory and application of various valuation models Asset pricing is becoming increasingly complex in today's financial markets. This guide to valuation arms investors with an introduction to the full range of modern valuation models and teaches them how to choose the right one for each asset valuation scenario, including real options, start-up firms, unconventional assets, private equity, and real estate funds.